Brain iron accumulation in Wilson's disease: A longitudinal imaging case study during anticopper treatment using 7.0T MRI and transcranial sonography. Issue 1 (4th April 2017) - Dusek, Petr; Skoloudik, David; Maskova, Jana; Huelnhagen, Till; Bruha, Radan; Zahorakova, Daniela; Niendorf, Thoralf; Ruzicka, Evzen; Schneider, Susanne A.; Wuerfel, Jens
Abstract : Level of Evidence: 5 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2018;47:282–285.